Clinical features of influenza-associated pulmonary aspergillosis: a retrospective multicenter cohort study - Shi, Jia-Xin; Shao, Xiang-Rong; Wu, Peng; Wang, Xiang; Sheng, Kui; Chen, Qi-Chao; Jin, Feng (Frontiers in Cellular and Infection Microbiology, 2025)
RationaleInfluenza-associated pulmonary aspergillosis (IAPA) is a great clinical challenge, which has high morbidity and mortality in severe influenza infections. Unlike invasive pulmonary aspergillosis (IPA), IAPA often occurs in immunocompetent hosts. That IAPA lacks of specific manifestations makes it difficult to diagnose and causes a high mortality rate, which is becoming challenges toclinicians. Exploring the clinical characteristics of IAPA in depth is of great significance for guiding clinical practice.ObjectivesTo determine the clinical features of IAPA in order to support appropriate clinical management of this public health threat.MethodsA retrospective multicenter cohort study was conducted. The clinical characteristics, risk factors, diagnostic methods, treatment, and prognosis data of the participants were analyzed.ResultsDiabetes and lymphopenia were important risk factors for IAPA. Pulmonary imaging showed that IAPA patients had more nodular lesions in the lungs, and a higher proportion of them were accompanied by cavitary lesions. The galactomannan (GM) test in bronchoalveolar lavage fluid (BALF) showed high sensitivity and specificity for diagnosing IPA. The positive rate of Aspergillus culture was relatively low, while microbiology rapid on-site evaluation (M-ROSE) could effectively detect mould with high specificity. The targeted next generation sequencing (tNGS) had important value in detecting Aspergillus with a sensitivity of 100% and a specificity of 86.7%. Both IAPA and Non-IAPA patients had a higher rate of co-infections, with a significantly higher co-infection rate of atypical pathogens in the IAPA group compared to the Non-IAPA group. The average treatment course for IAPA patients in the present study (32.2 ± 4.8d) was greatly shorter than the course specified in the IDSA (2016) guideline. The neutrophil to lymphocyte ratio (NLR) could effectively predict the prognosis of IAPA patients (cutoff value of NLR was 17.70, corresponding to a sensitivity of 0.87 and a specificity of 0.97).ConclusionsDiabetes and lymphopenia were important risk factors for IAPA. The comprehensive application of serum and BALF GM, M-ROSE and tNGS could significantly improve the detection rate of Aspergillus.